Emplacing Funsi: Antinomies of a District Capital and Transformation in Rural Ghana. Issue 1 (2nd January 2023) - Sabbi, Matthew
Abstract: Following ongoing debates on rural transformation, developing countries give priority to district capitals for their market viability and geographical centrality to empowering peripheral populations. Critics point out inherent electoral largesse in redistricting projects all the while ignoring hidden incentives from these exercises. Drawing on empirical data and local debates on decision dilemmas over a district capital in rural Ghana, the article raises two key points of interest. Rural district capitals undergird neither economic performance nor political participation of districts. A focus on their mundane governance processes, however, reveals hidden political incentives for local party buildout and individual political advancement. The insights enrich our understanding of in-built preferences in redistricting decisions beyond the widely perceived politico-economic attributes.